PSIKOLOGI KEBAHAGIAAN DENGAN PENDEKATAN NASH - Muhammad Tahir (Institut Agama Islam Negeri (IAIN) Manado, 2020)
ABSTRACTThe psychology of happiness with the nash approach aims to examine two things namely disaster and suffering whose purpose is to live happily. It is against this background that throughout human life only to achieve happiness. This type of research is a literature study with a nash approach. By using library data that is related to the discussion of psychology or discussion about happiness. The main reference in enriching the discussion on the psychology of happiness refers to the Qur'an and the Hadith. Based on the study of the text, it was found that the commands and prohibitions of religion are essentially aimed at making humans happy in the world and the hereafter. Therefore, humans must choose to live happily according to religious orders.Keywords: psychology, happiness, disaster, suffering.Â ABSTRAKPsikologi kebahagiaan dengan pendekatan nash bertujuan untuk mengkaji dua hal yakni musibah dan penderitaan yang tujuannya untuk hidup berbahagia. Hal tersebut dilatar belakangi bahwa sepanjang hidup manusia hanya untuk mencapai kebahagiaan. Jenis penelitian yang digunakan adalah studi literatur dengan pendekatan nash. Dengan menggunakan data-data pustaka yang ada kaitannya dengan pembahasan psikologi ataupun pembahasan tentang kebahagiaan. Refrensi utama dalam memperkaya pembahasan tentang psikologi kebahagiaan merujuk kepada nash al-Qurâ€™an dan Hadis. Berdasarkan kajian nash, didapati bahwa perintah dan larangan agama pada hakikatnya bertujuan agar manusia senantiasa berbahagia di dunia maupun di akhirat. Oleh karena itu, manusia wajib memilih untuk hidup bahagia sebagaimana perintah agama.Kata kunci: psikologi, kebahagiaan, musibah, penderitaan.